Formation Mechanism of Carbon-Supported Hollow PtNi Nanoparticles via One-Step Preparations for Use in the Oxygen Reduction Reaction - Kim, Dong-gun; Sohn, Yeonsun; Jang, Injoon; Yoo, Sung Jong; Kim, Pil (MDPI, 2022)
Hollow Pt-based nanoparticles are known to possess the properties of high electrocatalytic activity and durability. Nonetheless, their practical applications as catalytic materials are limited because of the requirement for exhaustive preparation. In this study, we prepared carbon-supported hollow PtNix (x = the moles of the Ni precursor to the Pt precursor in the catalyst preparation step) catalysts using a one-step preparation method, which substantially reduced the complexity of the conventional method for preparing hollow Pt-based catalysts. In particular, this hollow structure formation mechanism was proposed based on extensive characterizations. The prepared catalysts were examined to determine if they could be used as electrocatalysts for the oxygen reduction reaction (ORR). Among the investigated catalysts, the acid-treated hollow PtNi3/C catalyst demonstrated the best ORR activity, which was 3 times higher and 2.3 times higher than those of the commercial Pt/C and acid-treated particulate PtNi3/C catalysts, respectively.